Respuesta :
Hello!
The first step you would want to do here is distribute the -3 to inside the parentheses. This can be done by multiplying -3 by what's inside the parentheses. This would make the original equation become:
y + 1 = -3(x - 5)
y + 1 = (-3 * x) - (5 * -3)
Then, complete the multiplication inside the parentheses to get:
y + 1 = -3x + 15
Now, subtract both sides by 1 to isolate the y on the left side.
y + 1 - 1 = -3x + 15 - 1
Therefore, your final answer is:
y = -3x + 14
(it can also be f(x) = -3x + 14, y and f(x) are the same thing in this case)
Hope this helped!